Identification of Most Influential Parameters for Interactive Communication using DOE Technique - et. al., Syed Jawad Hussain, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Multimedia applications and platforms are widely being accepted in industry, business and academia as an alternative to classical communication equipment and techniques. Applications and platforms like distance learning, video conferencing, instant messaging, on-demand entertainment and group collaborations are the general usage areas. Advancement in the multimedia industry evolved around the development of infrastructure for delivery and algorithms for content compression. Though, end to end quality is not only affected by such factors. Customer Premises Equipment (CPE) and their particular configurations also play a vital role in the customer’s perceived quality i.e. Quality of Experience (QoE). An effort was required to identify the most influential parameters affecting an interactive communication application. Experiments conducted using Design of Experiment (DOE) technique which helped in the sensitivity analysis. In this study, three parameters Resolution Limit (RL), Scaling Factor (SF) and Frames per Seconds (FPS) were identified from the literature. The experiment was conducted in a controlled environment as per the L9 orthogonal array. Correlation and Fleiss Kappa were used for data validation whereas Signal to Noise Ratio (SNR) analysis was performed to identify the most influential parameter. SNR analysis helped us conclude that FPS is the most influential parameter that affects video quality at the CPE.